A magnesium-carbon dioxide battery catalyst material and preparation method

By using nitrogen-doped two-dimensional layered metal boride MBenes catalysts, the problems of high discharge product decomposition barrier and poor cathode catalyst effect in metal-carbon dioxide batteries are solved, and low overpotential and high performance of Mg-CO2 batteries are achieved. cycle life and cost-effective performance.

CN118099449BActive Publication Date: 2025-01-24YANSHAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410068878.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-17
Publication Date
2025-01-24
Estimated Expiration
2044-01-17

AI Technical Summary

Technical Problem

Existing metal-carbon dioxide batteries have problems such as high decomposition barrier for discharge products, poor cathode catalyst effect, small reserves and expensive prices, which affect their performance and large-scale applications.

Method used

The nitrogen -doped two -dimensional metal boron MBenes is used as a catalyst material. It adsorbs the nitrogen -based functional group and uses ultrasound, drying, and annealing to prepare a nitrogen doped MBenes catalyst with excellent performance.

Benefits of technology

A significant reduction of the excessive potential of the MG-CO2 battery, increasing the circulating life and discharge capacity, and the price is cheap, safe and environmentally friendly, suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118099449B_ABST
    Figure CN118099449B_ABST
Patent Text Reader

Abstract

The present application relates to the field of magnesium battery technology, and more specifically, to a magnesium-carbon dioxide battery catalyst material and a preparation method thereof. The magnesium-carbon dioxide battery catalyst material is a nitrogen-doped two-dimensional layered metal boride, wherein the two-dimensional layered metal boride is Mo 4 / 3 B 2‑x T z , MoB, Cr2B2, Cr2B4, Cr4B6, Ni2B, WB, Ti2B2, Fe2B2, Mn2B2, (Mo x ,Cr 1‑x )B、(Mo x ,W 1‑x )B、(Fe2,Cr 2‑x )B2, the nitrogen doping amount is 1wt.%-30wt.%, the magnesium-carbon dioxide battery catalyst material preparation method is to use MBenes and a nitrogen source as raw materials, adsorb nitrogen-based functional groups on the surface of MBenes by electrostatic adsorption, and obtain nitrogen-doped MBenes catalysts after subsequent ultrasound, drying, and annealing, and finally apply them to Mg-CO2 secondary batteries assisted by water. The water-assisted method can promote the generation of discharge products with crystal water, and the potential barrier is low and easy to decompose. The prepared nitrogen-doped MBenes catalyst has excellent performance and simple preparation. At the same time, the Mg-CO2 battery has an extremely low overpotential and a long cycle life, and is a carbon fixation green energy source with great development prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of magnesium batteries, and more specifically, to a magnesium-carbon dioxide battery catalyst material and a preparation method thereof. Background Art

[0002] Excessive use of fossil fuels has led to energy crises and excessive greenhouse gas emissions. Renewable and environmentally friendly energy sources, such as metal-CO2 batteries (such as Li-CO2, Na-CO2), are considered to be a new type of clean energy storage and greenhouse gas utilization strategy. Considering the safety hazards and poor stability of highly active monovalent alkali metals, magnesium (Mg) has attracted widespread attention as a more stable and abundant multivalent metal. At the same time, it has the advantages of relatively low redox potential (2.38V vs standard hydrogen electrode (SHE)), high theoretical capacity (3833mAh cm-3) and abundant resources. In addition, compared with alkali metals, Mg can fix more CO2 per cubic meter, which has a competitive advantage in price. Therefore, Mg-CO2 batteries have broad application prospects. However, due to the high decomposition barrier of discharge products, the performance of Mg-CO2 batteries is relatively poor. The above problems can be effectively solved by using water assistance (promoting the production of discharge products with crystal water, which are easy to adsorb and decompose) and selecting suitable catalysts.

[0003] Two-dimensional layered metal borides (MBenes) are pre-transition metal borides, new derivatives of ternary or quaternary layered transition metal borides (MAB) phases, and are a new type of two-dimensional planar material. MBenes have great application prospects in various fields due to their rich chemical properties, excellent reactivity, mechanical strength, stability, conductivity, transition properties, and energy harvesting possibilities. Especially in catalysis, various MBenes have been widely studied as electrocatalysts for reactions such as HER, OER, ORR, CO2RR, NRR, and NORR, and their performance exceeds that of traditional precious metal catalysts. In addition, heteroatom-doped two-dimensional materials are widely used in the fields of energy storage and catalysis as a multifunctional electrocatalyst. Therefore, using nitrogen-doped MBenes as cathode catalysts and water-assisted reduction of the energy barrier for the decomposition of discharge products will effectively improve the overpotential and cycle performance of Mg-CO2 batteries.

[0004] The document "Angewandte Chemie International Edition 2022, 134(17): e202200181" discloses a Mg-CO2 battery with CNT as cathode and water as auxiliary. At 200mAg-1, the minimum overpotential of the battery is 1.0V, but the cycle life is only 50 cycles. Although the document proposes that with the assistance of water, the decomposition product is converted into MgCO3·3H2O, which is easier to adsorb and decompose, the catalytic performance of CNT is very poor, resulting in unsatisfactory performance of the Mg-CO2 battery.

[0005] The document "Angewandte Chemie International Edition" 2020, 59(9): 3470-3474" discloses a rechargeable K-CO2 battery with potassium foil as anode and N-CNT / RGO as cathode. Although it can achieve a certain cycle, the discharge product K2CO3 is highly hygroscopic and unstable. In addition, potassium is expensive and active, and charging and discharging easily produce dendrites, which seriously affect the battery life, safety and universality.

[0006] Chinese invention patent application No. 201610211009.6 discloses a Na-CO2 room temperature secondary battery, which is a button battery assembled from a negative electrode shell, a spring, a gasket, a sodium sheet, a diaphragm, an electrolyte, a carbon dioxide-air electrode and a porous positive electrode shell, wherein the sodium sheet is the negative electrode, the carbon dioxide-air electrode is the positive electrode, and the carbon dioxide-air electrode is composed of a positive electrode catalyst and a current collector with a porous structure; the spring is a stainless steel sheet, which is used to fill the internal space of the battery to improve the battery airtightness; the gasket is a stainless steel sheet; the diaphragm is located between the negative electrode sodium sheet and the positive electrode current collector to block electron transmission; the electrolyte is a NaClO4 / tetraethylene glycol dimethyl ether (FEGDME) solution, and the electrolyte is infiltrated in the diaphragm. Although the secondary battery is reversible at room temperature and has a certain amount of capacity, it is difficult to mass produce due to the active nature of metallic sodium, poor controllability and high cost.

[0007] In summary, the main disadvantages of current metal-CO2 batteries are:

[0008] First, the decomposition barrier of discharge products is relatively high and difficult to decompose.

[0009] Second, lithium, sodium, and potassium metals are active in nature, making their storage and use complicated, and they are easily oxidized and spontaneously combust.

[0010] Third, the cathode catalyst is not effective, and new catalysts need to be explored.

[0011] Fourth, the small reserves and high prices seriously affect large-scale use. Summary of the invention

[0012] The present invention discloses a magnesium-carbon dioxide battery catalyst material and a preparation method, a nitrogen-doped MBenes catalyst, which has excellent performance and is simple to prepare. At the same time, the Mg-CO2 battery has an extremely low overpotential and a long cycle life, and is a carbon-fixing green energy source with great development prospects.

[0013] In a first aspect, the present disclosure provides a catalyst material for a magnesium-carbon dioxide battery, wherein the catalyst material is a nitrogen-doped two-dimensional layered metal boride.

[0014] Preferably, the two-dimensional layered metal boride is Mo 4 / 3 B 2-x T z , MoB, Cr2B2, Cr2B4, Cr4B6, Ni2B, WB, Ti2B2, Fe2B2, Mn2B2, (Mo x ,Cr 1-x )B、(Mo x ,W 1-x )B、(Fe2,Cr 2-x )One of B2.

[0015] Preferably, the doping amount of nitrogen in the catalyst material is 1wt.%-30wt.%.

[0016] Preferably, the catalyst material uses two-dimensional layered metal boride and nitrogen source as raw materials, and the nitrogen-based functional groups are adsorbed on the surface of MBenes by electrostatic adsorption, and then subjected to subsequent ultrasonication, drying, and annealing to obtain the N-MBenes catalyst.

[0017] In a second aspect, the present disclosure provides a method for preparing a catalyst material for a magnesium-carbon dioxide battery, comprising the following steps:

[0018] (1) Preparation of MAB: M powder, A powder and B powder were weighed according to the molar ratio, subjected to high temperature treatment and ball milling to obtain MAB powder;

[0019] (2) Preparation of MBenes: According to the chemical etching method, the MAB powder in step (1) is weighed into the HF solution, and then stirred at room temperature for 10-20 hours, and finally centrifuged at 3500-4000 rpm and dried at 80-100° C. for 10-12 hours to obtain MBenes;

[0020] (3) weighing the MBenes in step (2), and ultrasonically dispersing them in 45-50 mL of deionized water to form a MBenes suspension;

[0021] (4) weighing the nitrogen source according to the mass ratio of the MBenes suspension to the nitrogen source of 1:(1-10), and ultrasonically dispersing it in 45-50 mL of deionized water to form a nitrogen source suspension;

[0022] (5) Preparation of nitrogen-doped MBenes: slowly dripping the nitrogen source suspension in step (4) into the MBenes suspension in step (3), passing Ar protection, ultrasonicating at low temperature for 4-8 hours, centrifuging at 8000-10000 rpm, freeze-drying at minus 70-80°C for 24-36 hours, and finally annealing at 300-600°C in Ar for 2-4 hours to obtain a nitrogen-doped MBenes catalyst material.

[0023] Preferably, in step (1), the high temperature treatment is specifically: ball milling at a speed of 300-400 rpm for 4-8 hours, and then keeping the temperature at 1300-1600° C. and a pressure of 1-10 GPa for 20-60 minutes using a six-sided top press;

[0024] The MAB is (Mo 2 / 3 Y 1 / 3 )2AlB2, MoAlB, Cr2AlB2, Cr3AlB4, Cr4AlB6, Ni2ZnB, WAlB, Ti2InB2, Fe2AlB2, Mn2AlB2, (Mo x ,Cr 1-x )AlB、(Mo x ,W 1-x )AlB、(Fe2,Cr 2-x )One or two of AlB2.

[0025] Preferably, in step (2), the MBenes is Mo 4 / 3 B 2-x T z , MoB, Cr2B2, Cr2B4, Cr4B6, Ni2B, WB, Ti2B2, Fe2B2, Mn2B2, (Mo x ,Cr 1-x )B、(Mo x ,W 1-x )B、(Fe2,Cr 2-x ) one or two of B2; the concentration of HF is 40-49wt%.

[0026] Preferably, in step (4), the nitrogen source is one or two of cyanamide, dicyandiamide, melamine and urea.

[0027] In a second aspect, the present disclosure provides an application of a catalyst material for a magnesium-carbon dioxide battery, wherein the catalyst material is applied as a positive electrode catalyst material in a Mg-CO2 secondary battery.

[0028] Preferably, the method comprises the following application steps:

[0029] S1: The nitrogen-doped MBenes powder is ground with KB and PVDF in a mass ratio of (4-5):(5-3):(1-2) by N-methylpyrrolidone solvent for 0.5-1.0 h, coated on carbon paper, dried at 60-80° C. for 10-12 h, and then used with the aid of water;

[0030] S2: For Mg-CO2 battery positive electrode catalyst, wherein CO2 gas containing 1-10 vol% H2O is introduced into the battery device through a specific conduit and then led out from another outlet to keep the gas flowing; the Mg-CO2 battery discharge product specifically includes one or two of MgCO3·H2O, MgCO3·2H2O, MgCO3·3H2O, MgCO3·4H2O, and MgCO3·5H2O.

[0031] In summary, this application has the following beneficial effects:

[0032] 1. Since the nitrogen doping amount in the nitrogen-doped two-dimensional layered boride in the present application is high, the nitrogen doping amount is controllable, and the catalytic efficiency is excellent;

[0033] 2. In this application, with the assistance of flowing water, the discharge product has greater adsorption energy, which promotes its generation and decomposition;

[0034] 3. The Mg-CO2 battery assembled with nitrogen-doped MBenes prepared in this application has extremely low overpotential, high discharge capacity and long cycle life;

[0035] 4. The Mg-CO2 battery assembled with nitrogen-doped MBenes prepared in this application is cheap, safe, environmentally friendly, and easy to mass produce.

[0036] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not intended to limit the scope of protection of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 Mo prepared in Example 1 of the present application 4 / 3 B 2-x Scanning topography of

[0038] Figure 2 It is the nitrogen-doped Mo in Example 1 of the present application. 4 / 3 B 2-x Mg-CO2 battery performance diagram when used as positive electrode;

[0039] Figure 3 is a scanning morphology image of nitrogen-doped Mn2B2 prepared in Example 2 of the present application;

[0040] Figure 4is a transmission electron microscope image of nitrogen-doped MoB in Example 3 of the present application;

[0041] Figure 5 This is the energy spectrum of nitrogen-doped MoB in Example 3 of the present application. DETAILED DESCRIPTION

[0042] The present application is further described in detail below in conjunction with the examples. It is particularly noted that if no specific conditions are specified in the following examples, the experiments are carried out according to conventional conditions or the conditions recommended by the manufacturer. Unless otherwise specified, the raw materials used in the following examples can be obtained from common commercial sources.

[0043] Example

[0044] Example 1

[0045] (1) Preparation (Mo 2 / 3 Y 1 / 3 )2AlB2: Mo powder, Y powder, Al powder and B powder were weighed in the corresponding molar ratio of 4:2:3:6, ball milled at 300 rpm for 4 h, and then kept warm at 1300 ° C and 1 GPa for 20 min using a six-sided top press. Finally, ball milled at 300 rpm for 6 h to obtain (Mo 2 / 3 Y 1 / 3 )2AlB2 powder;

[0046] (2) Preparation of Mo 4 / 3 B 2-x According to the chemical etching method, first weigh 1.0g (Mo 2 / 3 Y 1 / 3 )2AlB2 powder was added to 10 mL of HF solution, then stirred at room temperature for 10 h, centrifuged at 3500 rpm, and dried at 80 °C for 10 h to obtain Mo 4 / 3B 2-x ;

[0047] (3) Weigh 0.5 g Mo from step (2) 4 / 3 B 2-x , ultrasonically dispersed in 45 mL of deionized water to form a uniform suspension;

[0048] (4) According to the mass ratio Mo 4 / 3 B 2-x : cyanamide is 1:1, weigh 0.5g of cyanamide, and ultrasonically disperse it in 45mL of deionized water to form a uniform suspension;

[0049] (5) Preparation of nitrogen-doped Mo 4 / 3 B 2-x : The cyanamide suspension in step (4) is slowly dripped into the Mo in step (3) 4 / 3 B 2-xThe suspension was protected by Ar, ultrasonicated at low temperature for 4 h, centrifuged at 8000 rpm, freeze-dried at -70 °C for 24 h, and finally annealed at 300 °C in Ar for 2 h to obtain nitrogen-doped Mo. 4 / 3 B 2-x Catalyst materials;

[0050] (6) The catalyst powder in step (5) was ground with KB and PVDF in a mass ratio of 4:5:1 by N-methylpyrrolidone solvent for 0.5 h, coated on carbon paper, dried at 60°C for 10 h, and then used as a positive electrode catalyst for Mg-CO2 batteries with the assistance of water. CO2 gas containing 1 vol% H2O was introduced into the battery device through a specific conduit and then led out from another outlet to keep the gas flowing.

[0051] Example 2

[0052] (1) Preparation of Mn2AlB2: Mn powder, Al powder and B powder were weighed in a corresponding molar ratio of 2:1:2, ball-milled at 400 rpm for 8 h, and then kept at 1500°C and 5 GPa for 40 min using a six-sided top press. Finally, Mn2AlB2 powder was obtained by ball-milling at 400 rpm for 8 h;

[0053] (2) Preparation of Mn2B2: According to the chemical etching method, first weigh 1.1 g of Mn2AlB2 powder in step (1) into 20 mL of HF solution, then stir at room temperature for 20 h, finally centrifuge at 4000 rpm, and dry at 100 °C for 12 h to obtain Mn2B2;

[0054] (3) Weigh 0.6 g of Mn2B2 from step (2) and disperse it in 50 mL of deionized water by ultrasonic to form a uniform suspension;

[0055] (4) According to the mass ratio of Mn2B2: dicyandiamide of 1:10, 6.0 g of dicyandiamide was weighed and ultrasonically dispersed in 50 mL of deionized water to form a uniform suspension;

[0056] (5) Preparation of nitrogen-doped Mn2B2: slowly dripping the dicyandiamide suspension in step (4) into the Mn2B2 suspension in step (3), passing Ar protection, ultrasonicating at low temperature for 8 h, centrifuging at 10,000 rpm, freeze-drying at minus 80°C for 36 h, and finally annealing at 600°C in Ar for 4 h to obtain a nitrogen-doped Mn2B2 catalyst material;

[0057] (6) The catalyst powder in step (5) was ground with KB and PVDF in a mass ratio of 5:3:2 by N-methylpyrrolidone solvent for 1.0 h, coated on carbon paper, dried at 80°C for 12 h, and then used as a positive electrode catalyst for Mg-CO2 batteries with the assistance of water. CO2 gas containing 5 vol% H2O was introduced into the battery device through a specific conduit and then led out from another outlet to keep the gas flowing.

[0058] Example 3

[0059] (1) Preparation of MoAlB: Mo powder, Al powder and B powder were weighed in a corresponding molar ratio of 1:1:1, respectively, ball-milled at 300 rpm for 4 h, and then kept at 1600°C and 10 GPa for 60 min using a six-sided top press. Finally, MoAlB powder was obtained by ball-milling at 300 rpm for 6 h;

[0060] (2) Preparation of MoB: According to the chemical etching method, first weigh 1.0 g of MoAlB powder in step (1) into 10 mL of HF solution, then stir at room temperature for 10 h, finally centrifuge at 3500 rpm and dry at 80 °C for 10 h to obtain MoB;

[0061] (3) Weigh 0.5 g of MoB from step (2) and ultrasonically disperse it in 45 mL of deionized water to form a uniform suspension;

[0062] (4) weighing 0.5 g of melamine at a mass ratio of MoB to melamine of 1:1, and ultrasonically dispersing it in 45 mL of deionized water to form a uniform suspension;

[0063] (5) Preparation of nitrogen-doped MoB: The melamine suspension in step (4) was slowly dripped into the MoB suspension in step (3), and Ar was introduced for protection. The mixture was ultrasonicated at low temperature for 4 h, centrifuged at 8000 rpm, freeze-dried at -70°C for 24 h, and finally annealed at 300°C in Ar for 2 h to obtain a nitrogen-doped MoB catalyst material.

[0064] (6) The catalyst powder in step (5) was ground with KB and PVDF in a mass ratio of 4:5:1 by N-methylpyrrolidone solvent for 0.5 h, coated on carbon paper, dried at 60°C for 10 h, and then used as a positive electrode catalyst for Mg-CO2 batteries with the assistance of water. CO2 gas containing 10 vol% H2O was introduced into the battery device through a specific conduit and then led out from another outlet to keep the gas flowing.

[0065] like Figure 1 The Mo obtained after HF etching in Example 1 is shown in FIG. 4 / 3 B2-x Scanning morphology shows that the surface is smooth and thin-layered, providing a good substrate for subsequent nitrogen doping.

[0066] like Figure 2 As shown, the catalyst in Example 1 is nitrogen-doped Mo 4 / 3 B 2-x Mg-CO2 battery performance diagram. From the performance diagram, it can be seen that at high current density (500mAg -1 ), the cycle life is excellent and can reach 150 cycles.

[0067] like Figure 3 Shown is a scanning electron microscope image of the nitrogen-doped Mn2B2 obtained in Example 2. It can be clearly seen that the surface presents a wrinkled and porous morphology, which can provide more active sites and improve the catalytic performance.

[0068] like Figure 4 , which is a transmission electron microscope image of nitrogen-doped MoB in Example 3, it can be seen that the morphology is wrinkled and porous.

[0069] like Figure 5 As shown, it is the energy spectrum diagram of nitrogen-doped MoB in Example 3. It can be clearly seen that the three elements Mo, B and N are evenly dispersed, which indirectly provides higher catalytic performance.

[0070] Comparative Example

[0071] Comparative Example 1

[0072] The catalyst material of the magnesium-carbon dioxide battery was prepared according to the method of Example 1, except that the metal boride was not a two-dimensional layered material, but a three-dimensional bulk commercial MoB, and no nitrogen doping was performed. Due to the small specific surface area and the lack of nitrogen doping to optimize the electronic structure, a serious lack of catalytic active sites was caused, which further reduced the electrochemical reaction efficiency and increased electrode polarization, resulting in poor performance of the magnesium-carbon dioxide battery.

[0073] Comparative Example 2

[0074] The catalyst material of the magnesium-carbon dioxide battery is prepared according to the method of Example 1, except that the two-dimensional layered material is not a metal boride, but a metal carbide Mo2C. Although the doping of nitrogen can also change the electronic structure of Mo2C, due to the special electronic orbit and large electronegativity of the boron element, the catalytic performance of the nitrogen-doped two-dimensional metal boride is far superior to that of the two-dimensional metal carbide. Therefore, the catalytic performance of the nitrogen-doped two-dimensional metal carbide catalyst is relatively low, resulting in a reduced cycle life of the battery. In the long-term cycle process, the electrode material may degrade, affecting the long-term stability of the battery.

[0075] The above is only an exemplary embodiment of the present disclosure, but the protection scope of the present disclosure is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present disclosure should be included in the protection scope of the present disclosure. Therefore, the protection scope of the present disclosure should be based on the protection scope of the claims.

Claims

1. Application of a nitrogen-doped two-dimensional layered metal boride as a positive electrode catalyst for a magnesium-carbon dioxide battery, characterized in that: The two-dimensional layered metal boride is Mo 4 / 3 B 2-x T z , MoB, Cr2B2, Cr2B4, Cr4B6, Ni2B, WB, Ti2B2, Fe2B2, Mn2B2, (Mo x ,Cr 1-x )B、(Mo x ,W 1-x )B、(Fe2,Cr 2-x )B2; The nitrogen doping amount of the nitrogen-doped two-dimensional layered metal boride is 1 wt.%-30 wt.%; The nitrogen-doped two-dimensional layered metal boride uses a two-dimensional layered metal boride and a nitrogen source as raw materials, and the nitrogen-based functional groups are adsorbed on the surface of the two-dimensional layered metal boride by electrostatic adsorption, and then subjected to subsequent ultrasonication, drying, and annealing to obtain the nitrogen-doped two-dimensional layered metal boride; The application comprises the following steps: S1: Weigh nitrogen-doped two-dimensional layered metal boride powder, KB, and PVDF according to the mass ratio of (4-5):(5-3):(1-2), grind them with N-methylpyrrolidone solvent for 0.5-1.0 h, coat them on carbon paper, dry them at 60-80 ºC for 10-12 h to obtain the positive electrode, and assemble the magnesium-carbon dioxide battery; S2: Introduce CO2 gas containing 1-10 vol% H2O into the battery device through a conduit, and then lead it out from another outlet to keep the gas flowing; the discharge products of the magnesium-carbon dioxide battery include one or two of MgCO3•H2O, MgCO3•2H2O, MgCO3•3H2O, MgCO3•4H2O, and MgCO3•5H2O.

2. The use of the nitrogen-doped two-dimensional layered metal boride as a positive electrode catalyst for a magnesium-carbon dioxide battery according to claim 1, characterized in that: The method for preparing the nitrogen-doped two-dimensional layered metal boride comprises the following steps: (1) Preparation of MAB: M powder, A powder and B powder were weighed according to the molar ratio, subjected to high temperature treatment and ball milling to obtain MAB powder; (2) Preparation of two-dimensional layered metal boride: According to the chemical etching method, weigh the MAB powder in step (1) into the HF solution, then stir at room temperature for 10-20 h, finally centrifuge at 3500-4000 rpm, and dry at 80-100 ºC for 10-12 h to obtain a two-dimensional layered metal boride; (3) Weigh the two-dimensional layered metal boride in step (2), and ultrasonically disperse it in 45-50 mL of deionized water to form a two-dimensional layered metal boride suspension; (4) Weigh the nitrogen source in a mass ratio of two-dimensional layered metal boride to nitrogen source of 1:(1-10), and ultrasonically disperse it in 45-50 mL of deionized water to form a nitrogen source suspension; (5) Preparation of nitrogen-doped two-dimensional layered metal boride: slowly drip the nitrogen source suspension in step (4) into the two-dimensional layered metal boride suspension in step (3), pass Ar protection, ultrasonicate at low temperature for 4-8 h, centrifuge at 8000-10000 rpm, freeze-dry at -70-80 ºC for 24-36 h, and finally anneal at 300-600 ºC for 2-4 h in Ar atmosphere to obtain nitrogen-doped two-dimensional layered metal boride.

3. The use of the nitrogen-doped two-dimensional layered metal boride as a positive electrode catalyst for a magnesium-carbon dioxide battery according to claim 2, characterized in that: In step (1), the high temperature treatment is: ball milling at a speed of 300-400 rpm for 4-8 hours, and then keeping the temperature at 1300-1600 ºC and a pressure of 1-10 GPa for 20-60 minutes using a six-sided top press; The MAB is (Mo 2 / 3 Y 1 / 3 )2AlB2, MoAlB, Cr2AlB2, Cr3AlB4, Cr4AlB6, Ni2ZnB, WAlB, Ti2InB2, Fe2AlB2, Mn2AlB2, (Mo x ,Cr 1-x )AlB、(Mo x ,W 1-x )AlB、(Fe2,Cr 2-x )One of AlB2.

4. The use of the nitrogen-doped two-dimensional layered metal boride as a positive electrode catalyst for a magnesium-carbon dioxide battery according to claim 2, characterized in that: In step (2), the two-dimensional layered metal boride is Mo 4 / 3 B 2-x T z , MoB, Cr2B2, Cr2B4, Cr4B6, Ni2B, WB, Ti2B2, Fe2B2, Mn2B2, (Mo x ,Cr 1-x )B、(Mo x ,W 1-x )B、(Fe2,Cr 2-x )B2; the concentration of the HF solution is 40-49 wt%.

5. The use of the nitrogen-doped two-dimensional layered metal boride as a positive electrode catalyst for a magnesium-carbon dioxide battery according to claim 2, characterized in that: In step (4), the nitrogen source is one of cyanamide, dicyandiamide, melamine and urea.

Citation Information

Patent Citations

  • A Na-CO2 room temperature secondary battery and its preparation method

    CN105633511B

  • Preparation method of heteroion doped MBene composite material

    CN115818657A